Art Making From the HEART: A Pediatric Case Study About Coping and Distraction During Oncology Treatments. Issue 6 (December 2017) - Bultas, Margaret W.; Saini, Shermini; Marty, Justine; Hendricks-Ferguson, Verna L.
Abstract : Diagnosis and treatment of childhood cancers are a potentially traumatic time of both emotional and physical distress for affected children and parents. Psychosocial palliative care interventions are needed to assist children to cope with unpleasant adverse effects during oncology treatments. Positive distraction techniques, such as art making, have shown evidence to reduce perceived pain and anxiety responses during cancer treatments. This exemplar case study highlights benefits of implementing an art-making project with an 11-year-old girl undergoing treatment for neuroblastoma, using an innovative and developmentally appropriate activity called the heirloom art-making (HEART) intervention. In the HEART intervention, the child and parent choose a meaningful photograph or picture that is transformed into a paint-by-number canvas, providing a fun activity for the parent and child to focus on together. The completed painting can be kept as a cherished family keepsake. Art-making projects, such as the HEART, can potentially be used by nurses to foster developmentally appropriate, nonpharmacological, palliative care interventions to help children focus on secondary-control coping strategies (ie, distraction) during oncology treatments. Art-making projects also provide a fun mechanism to foster positive interactions between nurses and patients, an opportunity for parent involvement, and a sense of normalcy for child and parents during oncology treatments.